2021
DOI: 10.3389/fonc.2021.730412
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy as a Potential De-Escalation Strategy in Locally Advanced HPV-Associated Oropharyngeal Cancer: A Literature Review

Abstract: The treatment landscape of locally advanced HPV-oropharyngeal squamous cell carcinoma (OPSCC) is undergoing transformation. This is because the high cures rates observed in OPSCC are paired with severe treatment-related, long-term toxicities. These significant adverse effects have led some to conclude that the current standard of care is over-treating patients, and that de-intensifying the regimens may achieve comparable survival outcomes with lower toxicities. Consequently, several de-escalation approaches in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 127 publications
(270 reference statements)
0
6
0
Order By: Relevance
“…De-escalation strategies are currently being considered in several malignancies. The goals of de-escalation are reducing therapy-related toxicity, increasing or maintaining survival outcomes, and improving patients quality of life [46]. Indeed, the multimodal therapeutic approaches applied in HNSCC, including surgery, radiotherapy, and/or chemotherapy, are correlated with both acute and long-term toxicity.…”
Section: The Role Of Tils In the Elucidation Of De-escalation Therapi...mentioning
confidence: 99%
“…De-escalation strategies are currently being considered in several malignancies. The goals of de-escalation are reducing therapy-related toxicity, increasing or maintaining survival outcomes, and improving patients quality of life [46]. Indeed, the multimodal therapeutic approaches applied in HNSCC, including surgery, radiotherapy, and/or chemotherapy, are correlated with both acute and long-term toxicity.…”
Section: The Role Of Tils In the Elucidation Of De-escalation Therapi...mentioning
confidence: 99%
“…However, treatment-related morbidities and quality of life issues remain major concerns for survivors [1]. Long-term morbidities include dysphagia, xerostomia, ototoxicity, and trismus [6]. Head and neck cancer survivors have the second-highest suicide rate, surpassed only by pancreatic cancer, and are almost twice as likely to die from suicide compared to survivors of other cancers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Cetuximab has thus far been regarded as the most promising cisplatin substitute for HNSCC treatment in conjunction with radiation. However, in various recent clinical trials, cetuximab has shown inferior survival outcomes as compared to cisplatin, and this has dampened the hope of incorporating its use into de-intensified regimens for HPV-related HNSCC (15)(16)(17)(18). Together, these observations further underscore the need for greater efforts to discover and develop more robust and selective targeted agents.…”
Section: Discussionmentioning
confidence: 99%
“…However, because HPV-associated OPSCC has excellent outcomes, many now believe that the current standard dose is resulting in overtreatment of the HPV + patient cohort. Numerous endeavors to de-escalate the radiation treatment regimens are already underway with a goal of lowering toxicity without compromising clinical outcomes (3,11,(15)(16)(17)(18). Most de-escalation attempts thus far have revolved around limiting the toxicity inflicted by photon-based radiotherapy.…”
Section: Introductionmentioning
confidence: 99%